The 13th conference on Integrated Optics - Sensors, Sensing Structures and Methods IOS’2018 - Pustelny, Tadeusz (Photonics Letters of Poland, 2018)
The conference covers the topical areas of optics, optoelectronics and photonics in the following aspects: fundamental and applied research, physics and technical, materials, components and devices, circuits and systems, technological and design, construction and manufacturing of photonic devices and systems, and metrology.